The resolution of inter-state disputes in civil aviation - Zhang, Luping (Law teacher) (Oxford University Press, 2022)
This book investigates dispute resolution mechanisms in international civil aviation, with a primary focus on the functions of the International Civil Aviation Organization (ICAO) Council. The Convention on International Civil Aviation (Chicago Convention) has laid the foundation for dispute resolution mechanisms in international civil aviation, which led to the creation of ICAO. However, economic regulations have been left out from the Chicago Convention. Over the years there has been a proliferation of bilateral air services agreements (ASAs) and the multiplication of multilateral treaties. With the advancement of the aviation technology, this book considers whether dispute resolution mechanisms should be modernised, and if so, what form such modernisation might take. The book is divided into five chapters. Chapter I provides an introduction and defines the scope of the research. Chapter II is an empirical chapter, which traces the evolution of dispute resolution clauses under both multilateral air law treaties and bilateral ASAs with the most updated data collected to date. Chapter III analyses how disputes brought to the fora designated under the treaties in Chapter II are resolved in practice. The fourth chapter builds on the empirical evidence provided in Chapters II and III to critically assesses the political and legal means that are involved in the settlement of international aviation disputes. The final chapter proposes reforms on the basis of the lessons learnt in the previous chapters and introduces proposals for amending rules of procedures in ICAO as well as establishing a new arbitral institution"--